Pengaruh Aliran Nitrogen Kontinyu ke Dalam Reaktor Pirolisis Limbah Biomassa Serbuk Gergaji Batang Kelapa (Cocos Nucifera) Terhadap Nilai Kalor. - Syarwan Hamid; Andi Aladin; Basri Modding; Takdir Syarif; Lastri Wiyani; Muh Arman (Journal of Chemical Process Engineering, 2023)
AbstractThe potential amount of coconut sawdust biomass in Indonesia is very abundant, so far it has not been utilized optimally and tends to be wasted as waste. Coconut sawdust with the main composition of carbon contains heat equivalent to light coal, which is around 4400 kcal/kg. Even though its calorific value is still low, it has the potential to be used as a solid fuel source or an alternative energy source. The calorific value of coconut sawdust can be increased through the pyrolysis process. A study has been carried out on the effect of nitrogen inert gas flowing continuously into the pyrolysis reactor of coconut sawdust biomass waste (Cocos nucifera) on the calorific value of the resulting charcoal. The aim of the research is to determine the effect and optimum flow path of nitrogen inert gas which gives the maximum calorific value of charcoal product. From this study it was concluded that the continuous flow of inert nitrogen gas into the pyrolysis reactor had an effect on increasing the calorific value of the charcoal product by up to 4% compared to not using the inert gas. The optimum nitrogen gas flow rate is 2 L/minute giving a maximum effective calorific value of 7200 kcal/kg